Assessment of microplastic characterization and distribution from surface water and the seabed in the Flores Sea, Indonesia - Herawati, Titin; Damayanti, Windi; Yuda, Givanka A.; Ihsan, Yudi N.; Pasaribu, Buntora; Harsono, Gentio; Marlina, Marlina; Suseno, Heny; Mustopa, Rizki A.; Karya, Felin S. W.; Febriani, Choerunnisa; Purba, Noir P. (Frontiers in Marine Science, 2024)
Despite growing global concerns, there has been limited research on the characterization and distribution of microplastics in the Indonesian Throughflow (ITF) pathways such as the Flores Sea. The Flores Sea is a component of the Indian-Pacific Current (ITF) and has the capacity to carry pollution over large marine ecosystems, making this research extremely important. To respond to these concerns, this research aims to determine the characterization and distribution of microplastics (MPs) at six research sites in the Flores Sea that are precisely located within the ITF (Indonesia Throughflow). This work exhibits an extensive dataset focusing on the occurrence, attributes, and dispersion of microplastics in the Flores Sea, therefore providing significant contributions to the understanding of the environmental condition of this area. Here, we conduct the first survey on microplastics in the surface water and seabed in the Flores Sea and will provide a comprehensive data set on the presence, characteristics, and distribution of microplastics in the Flores Sea. Sea surface water samples were collected using a neuston net, while sediment samples were taken from three stations at the shallowest depth using the Ekman Grab sampler. Additionally, abundance, size, shape, and color analyses were conducted using a light microscope, and microplastic types were identified through Raman spectroscopy. The results indicated that the waters and sediment of the Flores Sea are polluted with microplastics, with relative abundances ranging from 0.75±0.49 to 2.13±0.25 item/l samples. The most dominant shapes identified were filament (77.45%) and fragment (13.40%), with sizes varying between surface water 4.70 to 3799.25 µm and seabed from 67.20 μm to 2176.87 μm, while black (30.07%) and blue (24.51%) were reported as the common MPs colors, the identified polymers include PET and PE. This study confirms visual evidence of microplastics in the open waters of eastern Indonesia. While it may not fully capture the wide range of temporal variations, it establishes initial levels of microplastic presence and dispersion. Given that the ITF influences both the Pacific and Indian Oceans, this research contributes to the global understanding of microplastic distribution, underscoring the need for coordinated international efforts to address marine pollution.